Behaviour features of the radiative losses of the torsatron U – 3M plasma - Kotsubanov, V.D.; Kulaga, A.E.; Nikolskij, I.K.; Pashnev, V.K.; Tsybenko, S.A. (Вопросы атомной науки и техники, 2006)
The total bolometrically measured plasma radiation losses on the RF heating power were found. The results of measurements demonstrate a nonmonotonic dependence of radiation losses on RF power. Namely, at low RF power levels (80...170 kW) the total radiation losses raised with increasing the RF power. However, the total radiation losses decreased sharply when RF power exceeded 200 kW (down to ≈20 kW at 240 kW of RF power). Simultaneously, the intensity of impurity lines fell down significantly, whereas the average electron temperature (found from ECE measurement) did increase. The authors consider that screening properties of periphery plasma give reasons for above experimental facts.